International Comparative Perspectives on Religion and Education - Wolhuter, Charl C.; De Wet, Corene (UJ Press, 2014)
This book scrutinises religion in education in ten countries. It reveals much about the tension between religion and education in secular countries, and the blending between religion and education in religious countries, such as Iran and Malaysia, as well as secular countries such as the Netherlands. It also shows the important role the church currently plays in education in developing countries, such as Tanzania.